Exploitation of agro-climatic zones to produce off-season fruits in Peninsular Malaysia - Karim, Mohd Zain; Mad, Hasan (1989)
In response to increasing demand both for local consumption as well as for export fruit cultivation in Malaysia is showing an increasing trend. Based on specific climatic and soil requirements of the various fruits and the identification of agro-ecological zones within Peninsular Malaysia it is possible to indicate the locations where each fruit type could be grown. This paper examines the suitable locations where durian (Durio zibethinus), starfruit (Averrhoa carambola), pineapple (Ananas comosus) and papaya (Carica papaya) can best be grown to meet the increasing demand.